A carbon responsive G‐protein coupled receptor modulates broad developmental and genetic networks in the entomopathogenic fungus, Beauveria bassiana. (1st July 2013) - Ying, Sheng‐Hua; Feng, Ming‐Guang; Keyhani, Nemat O.
Summary: In fungi, G‐protein coupled receptors (GPCRs) link ligand/nutrient sensing to growth, mating, developmental/life‐stage activation and pathogenesis. A GPCR was characterized from the entomopathogenic fungus, Beauveria bassiana ( BbGPCR3 ), which links nutrient sensing to stress response and development. Δ BbGPCR3 mutants grew slower on various carbohydrates and displayed increased sensitivity to osmotic, oxidative and cell wall stresses. Gene expression profiling revealed a set of heat‐shock and antioxidant factors that failed to be induced under oxidative stress and aberrant regulation of compatible solute‐forming enzymes and cell wall biosynthesis/remodelling proteins in Δ BbGPCR3 after osmotic stress. Glucose‐specific developmental defects included reduced (> 90%) conidiation and reduced dimorphic transition to the production of yeast‐like blastospores, effects suppressed in media containing trehalose or glycerol, but not by addition of cyclic AMP. Insect bioassays revealed reduced virulence in topical assays but no effect in intrahaemoceol injection assays, indicating that BbGPCR3 was important in sensing signals during the initial interaction with the host but dispensable for post‐penetration events. Comparative gene expression profiling of Δ BbGPCR3 mutants grown in glucose media compared with wild‐type/glucose and Δ BbGPCR3 /trehalose grown cells revealed sets of genes misregulated and recovered, respectively. These data link BbGPCR3 to broad developmental and genetic networks that include the major MAP kinase pathways.